ASAS TERBUKA UNTUK UMUM DAN KEHADIRAN FISIK PARA PIHAK DALAM SIDANG DI PENGADILAN NEGERI PASCA PERATURAN MAHKAMAH AGUNG NOMOR 1 TAHUN 2019 - Waluyo, Bernadette M (Faculty of Law, Parahyangan Catholic University, 2020)
The Indonesian Supreme Court, in response to the information era, modernizes the civil procedural rules at the district court level. This is done by issuing Supreme Court Regulation no. 1 of 2019 re. Administration of Justice at Civil Law Courts and Electronic-Court Proceedings. Undoubtedly, modernization of existing rules on the administration of justice is much needed. On the other hand, these changes may violate a number of procedural civil law principles. The author argues, from a civil procedural law perspective, that the above Supreme Court regulation violates the basic principle of transparency of court proceedings and physical attendance at court proceedings.